The potential of methylxanthine-based therapies in pediatric respiratory tract diseases. (March 2016) - Oñatibia-Astibia, Ainhoa; Martínez-Pinilla, Eva; Franco, Rafael
Abstract: Caffeine, theophylline and theobromine are the most known methylxanthines as they are present in coffee, tea and/or chocolate. In the last decades, a huge experimental effort has been devoted to get insight into the variety of actions that these compounds exert in humans. From such knowledge it is known that methylxanthines have a great potential in prevention, therapy and/or management of a variety of diseases. The benefits of methylxanthine-based therapies in the apnea of prematurity and their translational potential in pediatric affections of the respiratory tract are here presented. Highlights: Methylxanthines are natural products used to combat airway diseases. Complementary molecular mechanisms are necessary for methylxanthine efficacy. Methylxanthine are safe and may be used even in the apnea of prematurity. Methylxanthines act locally on airways and centrally on respiratory control centers.